Hijabisasi dalam Pernikahan Adat Jawa (Fenomena Pemakaian Hijab dalam Pernikahan Adat Jawa di Desa Jabalsari Kecamatan Sumbergempol Kabupaten Tulungagung - Moh Davidin (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2023)
Hijab is generally stated as a head cover or protector for women, which basically functions to cover the genitals, in this case the hijab is a common garment that is known by the Muslim community, previously the hijab was clothing that was considered less modern or old-fashioned, but now as a fashion trend in clothing, the development of the hijab has become very popular in society and in its development the hijab has various variations in fashion, one of which is the hijab used in traditional Javanese weddings. This study discusses Hijabization in Javanese Traditional weddings in Jabalsari Village, the purpose of this research is to find out the phenomenon of wearing hijab in Javanese Traditional Weddings in Jabalsari Village, this research is a descriptive qualitative research based on field study research, data collection using the interview method which was analyzed through theory of Social Construction Peter L Berger and Lukman. The results of the study are the development of the use of the hijab not only to protect the head and cover the genitals, but also as a lifestyle trend among the public, especially among women, the hijab is also used for brides in Javanese Traditional weddings, whose use already exists and is a trend that Widely developed in Javanese society, the existence of the hijab has become a magnet in itself and is a form of change in fashion attire in traditional Javanese weddings.